Pengaruh Substitusi Maizena dan Penambahan Puree Kelor (Moringa oleifera lam) Terhadap Sifat Sensori Sosis Gurame - Fibta Ika Agustin; Sri Handajani; Niken Purwidiani; Lucia Tri Pangesthi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The sausages available on the market today from beef, chicken, and fish sausages contain little nutritional content. To increase and increase the nutritional content of sausages, you can use an animal protein source with high nutritional content, namely carp. In this study, carp sausage will be created with cornstarch substitution and the addition of moringa puree which has a high nutritional content to improve nutrition in sausages. The purpose of this study is to determine the effect of cornstarch substitution and the addition of moringa puree on the sensory properties of carp sausage. The research method used was in the form of a preference test with 30 panelists. The samples to be studied are 6, namely with 25% and 50% cornstarch substitution and the addition of 5%, 10%, and 15% moringa puree. The data results will be analyzed with two-way anova and Duncan tests. The results of the analysis showed that the best product was with 25% cornstarch substitution and 15% moringa puree.